A novel PMP22 insertion mutation causing Charcot–Marie–Tooth disease type 3: A case report. Issue 11 (19th March 2021) - Han, Liang; Huang, Yanjing; Nie, Yuan; Li, Jing; Chen, Gang; Tu, Shenghao; Shen, Pan; Chen, Chao
Abstract: Rationale: Charcot–Marie–Tooth disease (CMT) is a group of hereditary neuropathies with clinical features of muscle atrophy, sensory loss, and foot deformities. CMT is related to a number of genes, such as peripheral myelin protein 22 gene ( PMP22 ). Missense mutations, small deletion mutations, and duplications of PMP22 are common in CMT patients, but few insertion mutation cases of PMP22 have been reported. Patient concerns: A 26-year-old male patient with the complaint of general weakness, peroneal atrophy, and deformities in the extremities visited our hospital. The patient was born with bilateral thumbs and feet dystonia. Additionally, delayed feet arch development and delayed walking was observed when he was a child. Diagnosis: Using whole-exome sequencing and electrophysiological test, we identified a novel insertion mutation of PMP22 (NM_153322, c.54_55insGTGCTG, p.(L19delinsVLL)) in a 26-year-old male patient with peroneal atrophy and nerve conduction was not elicited in electromyography (EMG) study. The Protein Variation Effect Analyzer ( PROVEAN ) program analysis predicted that the variant is likely to be "deleterious." SWISS-MODEL program predicted that alpha helix in original location was disrupted by inserted 6 bases, which may account for the occurrence of CMT3. Interventions: The patient received symptomatic and supportive treatments, and routine rehabilitation exercises during hospitalization. Outcomes: The condition of the patient was improved, but the disease could not be cured. At 1- and 3-months follow-up, manifestations of the patient were unchanged, and he could take care of himself. Lessons: Our findings link a novel PMP22 mutation with a clinical diagnosis of CMT3. The link between gene variation and CMT phenotype may help to reveal the structure and function of PMP22 protein and the pathogenesis of CMT. This study adds further support to the heterogeneity of PMP22 related CMT and provides solid functional evidence for the pathogenicity of the p.(L19delinsVLL) PMP22 variant. Moreover, with the development of high-throughput sequencing technology, the combination of next-generation sequencing (NGS) and conventional Sanger sequencing is becoming one of the comprehensive, inexpensive, and convenient tools for genetic diagnosis of CMT.